2014
DOI: 10.5120/15963-5155
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and Detection of Diabetic Retinopathy Exudates

Abstract: Diabetic retinopathy, the most common diabetic eye disease, occurs when blood vessels in the retina change. Sometimes these vessels swell and leak fluid or even close off completely. In other cases, abnormal new blood vessels grow on the surface of the retina. Early detection can potentially reduce the risk of blindness. This paper presents an automated method for the detection of exudates in retinal color fundus images with high accuracy, First, the image is converted to HSI model, after preprocessing possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The authors suggested a back-propagation-based neural network for twoclass classifications. Similarly, in [12], multilayer perception neural network (MLPNN) was used to detect DR. An automatic exudate detection approach was developed in [13], where optic disk (OD) segmentation was performed using a graph cuts algorithm. The authors in [13] used the invariant moments Hu to extract the feature vector and NN-based two classes; exudate and non-exudate classification was performed.…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors suggested a back-propagation-based neural network for twoclass classifications. Similarly, in [12], multilayer perception neural network (MLPNN) was used to detect DR. An automatic exudate detection approach was developed in [13], where optic disk (OD) segmentation was performed using a graph cuts algorithm. The authors in [13] used the invariant moments Hu to extract the feature vector and NN-based two classes; exudate and non-exudate classification was performed.…”
Section: Literature Surveymentioning
confidence: 99%
“…Bhatkar and Kharat [23] applied a deep neural network based on multilayer perception. On the basis of optic disk segmentation, an automatic computer aided detection approach was developed [24] with the graph cuts technique. Raman et al [25], used optic disk identification for microaneurysm and exudate features extraction to classify the DR images.…”
Section: Introductionmentioning
confidence: 99%
“…The image containing exudates are shown in Figure 1. Elbalaoui, M. Fakir, and A. Merbouha [1] proposed an automated method for the detection of exudates in retinal color fundus images. First, the image is converted to HSI model, after pre-processing possible regions containing exudate, the optic disk is detected using Hough transform.…”
Section: Introductionmentioning
confidence: 99%